Aktualne tendencje przestępczość narkotykowej oraz zażywania narkotyków wśród nieletnich w Polsce - Stachelska, Aleksandra (PRAWO i WIĘŹ, 2025)
This paper examines the growing problem of drug-related crime and the use of psychoactive substances among minors in Poland. Based on court statistical data and recent survey studies, it explores shifting behavior patterns and identifies factors contributing to this trend. Special emphasis is placed on the social and psychological influences, as well as the increasing availability of new synthetics drugs such as mephedrone and fentanyl. The findings highlight the need for effective preventive measures and support systems to curb the escalation of this problem.